STUDY OF THE CHEMICAL COMPOSITION OF ESSENTIAL OIL OBTAINED FROM LAVENDER (LAVANDULA ANGUSTIFOLIA) - Jalilov Fazliddin Sodiqovich; Zokirjonov Asilbek Dilshodjonovich (Innovate Conferences, 2025)
Lavender (Lavandula angustifolia) is one of the most widely used medicinal plants in both human health and the cosmetics industry. The essential oil obtained from this plant is well known for its calming, antiseptic, antibacterial, and anti-inflammatory properties. Due to these characteristics, lavender essential oil is widely used in the pharmaceutical and cosmetics industries, as well as in alternative medicine.Lavender contains numerous biologically active compounds. Understanding its chemical composition and properties is crucial for ensuring its effective and safe application. Comprehensive knowledge of essential oil components and their effects is necessary to maximize their benefits across different fields.Given its unique properties and high efficiency, studying the chemical composition of lavender essential oil is of great scientific and industrial importance. Research on essential oils helps unlock their full potential, facilitate the development of new pharmaceutical and cosmetic products, and enhance their safety.Lavender essential oil is particularly valuable in medicine for reducing stress, improving sleep, alleviating inflammation, and treating skin disorders. Therefore, an in-depth study of its chemical composition is essential for expanding its applications in medical and cosmetic fields and for developing effective natural-based pharmaceutical preparations. This research is not only important for academic science but also holds significant value for the pharmaceutical and cosmetics industries.